2019
DOI: 10.1016/j.jaci.2018.11.041
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of clinical benefit from treatment with mepolizumab for patients with eosinophilic granulomatosis with polyangiitis

Abstract: GRAPHICAL ABSTRACT eosinophils BVAS, Birmingham Vasculitis Activity Score; D, day; GC, Glucocorticoids (prednisone/prednisolone); MoA, mechanism of action Eosinophil Mepolizumab MoA for mepolizumab CLINICAL BENEFIT: DEFINITION 1 CLINICAL BENEFIT: DEFINITION 2 87% MEPOLIZUMAB vs 53% PLACEBO Remission (BVAS 0 and ≤4 mg/d GC) or ≥50% reduction in GC dose or relapse-free Remission (BVAS 0 and ≤7.5 mg/d GC) or ≥50% reduction in GC dose or relapse-free 78% MEPOLIZUMAB vs 32% PLACEBO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 20 publications
0
57
0
5
Order By: Relevance
“…Eosinophils are generally believed to play important roles in the pathogenesis of certain allergic or inflammatory disorders. For example, anti-interleukin (IL)-5 treatments that selectively attenuate the number and functional status of eosinophils dramatically improve disease control of severe bronchial asthma with eosinophilia or eosinophilic granulomatosis with polyangiitis [1,2]. In a murine model of asthma, a lack of eosinophils is sufficient to abolish airway remodeling [3].…”
Section: Introductionmentioning
confidence: 99%
“…Eosinophils are generally believed to play important roles in the pathogenesis of certain allergic or inflammatory disorders. For example, anti-interleukin (IL)-5 treatments that selectively attenuate the number and functional status of eosinophils dramatically improve disease control of severe bronchial asthma with eosinophilia or eosinophilic granulomatosis with polyangiitis [1,2]. In a murine model of asthma, a lack of eosinophils is sufficient to abolish airway remodeling [3].…”
Section: Introductionmentioning
confidence: 99%
“…Akin to eotaxin‐1, a serum to lesional gradient is present for IL‐5 that together may explain the highly localized and destructive cellular infiltrates formed in BP . Immunotherapies directed at neutralizing IL‐5 have been trialed in several hypereosinophilic diseases, and mepolizumab, an anti‐IL5 antibody, is currently FDA approved for asthma and eosinophilic granulomatosis with polyangiitis . Its efficacy in BP is currently under investigation in a phase II, randomized, placebo‐controlled, double‐blind study (NCT01705795).…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
“…In a recent article Steinfeld et al 1 reported the results of post hoc assessment of clinical benefit of mepolizumab, an mAb that targets IL-5, in patients with relapsing/refractory eosinophilic granulomatosis with polyangiitis (EGPA) using data from a randomized, placebo-controlled, double-blind, parallel-group trial Mepolizumab In Relapsing or Refractory EGPA (MIRRA). Organ-threatening EGPA and life-threatening EGPA (eg, with rapidly progressive glomerulonephritis, diffuse alveolar hemorrhage, and severe cardiac disease) were exclusion criteria.…”
Section: To the Editormentioning
confidence: 99%